NucS and drug resistance in Mycobacterium tuberculosis: potential for novel therapeutic targets - Yakupov , B.Sh.; Zein , U.O.; Turgimbayeva, A.M.; Abeldenov , S.K. (Eurasian Journal of Applied Biotechnology, 2025)
Antibiotic resistance of Mycobacterium tuberculosis poses a serious threat to global health. Kazakhstan is among the top 30 countries with the highest levels of multidrug-resistant tuberculosis and rifampicin-resistant tuberculosis. Existing antibiotics are losing effectiveness due to the rapid growth of drug resistance, which is why DNA repair enzymes of the pathogen are being considered as promising targets for new antibiotics. Unlike many other bacteria, M. tuberculosis lacks the classical mismatch repair system; instead, it employs an alternative pathway mediated by the endonuclease NucS. This article discusses the role of NucS in maintaining genomic stability in M. tuberculosis and its involvement in the development of antibiotic resistance. A review of experimental data shows that inactivation of NucS leads to a hypermutator phenotype, increasing the likelihood of the emergence of drug-resistant strains. These properties make NucS a promising target for antibacterial therapy. The study of NucS as a critically important protein in the pathogenesis and resistance of M. tuberculosis opens new avenues for the development of targeted drugs and strategies to suppress the development of resistance.